Predictors of Self-Efficacy in Therapeutic Communication among Novice Nurses vs. Experienced Nurses: A Study of 100 Nurses at Dr. Sudiran Mangun Sumarso General Hospital - Susana Nurtanti; Sri Handayani; Putri Halimu Husna (International Journal Of Health Science, 2026)
An overview of the object of research to are self-efficacy in therapeutic communication is a crucial competency for nurses to provide patient-centered care and ensure effective interactions during clinical practice. Differences in clinical experience can influence predictors of self-efficacy in therapeutic communication. Research objectives to analyze predictors of self-efficacy in therapeutic communication among novice and experienced nurses at dr. Soediran Mangun Sumarso General Hospital, Wonogiri. Proposed methods is A quantitative analytical cross-sectional study was conducted among 100 nurses selected using stratified proportional random sampling. Data were collected using the Self-Efficacy in Therapeutic Communication for Nurses (SETC-N) questionnaire and analyzed using multiple linear regression. Results: Predictors significantly associated with self-efficacy among novice nurses included work stress (β = −0.312, p < 0.05) and communication training (β = 0.421, p < 0.01). Among experienced nurses, organizational support (β = 0.388, p < 0.01) and empathy (β = 0.274, p < 0.05) were the strongest predictors. The total explained variance was 52.6% for novice nurses and 48.2% for experienced nurses. Conclusion: Predictors of communication self-efficacy differ between novice and experienced nurses. These findings underscore the need for targeted interventions based on experience level to strengthen communication competency.